(3GdGKfG YTQjI aj GdRcGI hGdNeSs - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3MeOG dc Gddge Ydi Lejd BdGFc hLRjd fYeGFc hUdhI Ydi CTQa CfHjGFc (B... (3gPg KGdKI GdGKfi YTQjGJ GdNeS JJdh Ydjc Gdege ef eSGFd GdRcGI hGdNeS Ydi JQJjH LOjO (B... (3GdRcGI EeG eJYdbI HGdeGd hgj GdeGdjIs
(3BNQgG (B:s
(3BNQgG(B: (3Ke eSJMb GdNeS GdEeGe hGdgGTejhf, CeG aj GdjJGei hGdeSGcjf hGHf GdSHjd hgh Hjfg hHjfge fUaGf hjTJQW EjeGfge dG YOGdJge hjJhdi fGFH GdZjHI UQa MUJg Zdjge heY MVhQg SdGe Gddg Ydjg jUQa Gdcd Zdjg hGdRjGOI Yf caGjJge dg hGdfbjUI Ydjg YLd Gddg aQLg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B1: 81s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis